2012
DOI: 10.1111/j.1365-2648.2012.06126.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to dietary habits and body mass index among Turkish school children: a Cox's interaction model‐based study

Abstract: Nurses are well-situated to give children dietary self-efficacy improvement, dietary attitude enhancement, and family-centred and school-based intervention programmes to reduce their unhealthy dietary habits. The model guides researchers to identify the background characteristics of children that result in the body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 52 publications
4
17
0
2
Order By: Relevance
“…A higher score indicates a higher self-efficacy. The Turkish validity and reliability study of the scale was conducted by Haney and Erdoğan (2013) [8]. Its reliability coefficient was 0.79, the testretest reliability was 0.68; it was found to be 0.77 in the present study.…”
Section: Children's Dietary Self-efficacy Scalesupporting
confidence: 50%
“…A higher score indicates a higher self-efficacy. The Turkish validity and reliability study of the scale was conducted by Haney and Erdoğan (2013) [8]. Its reliability coefficient was 0.79, the testretest reliability was 0.68; it was found to be 0.77 in the present study.…”
Section: Children's Dietary Self-efficacy Scalesupporting
confidence: 50%
“…A higher score indicates higher self-efficacy. The Turkish validity and reliability study of the scale was conducted by Haney and Erdoğan (2013). Its reliability coefficient was 0.79 and the test-retest reliability was 0.68; it was found to be 0.77 in the present study.…”
Section: 34children's Dietary Self-efficacy Scalesupporting
confidence: 46%
“…As Father's educational level, Mother's BMI and Father's BMI increase, the rate of overweight/obese adolescents increases. The studies have shown that dietary habits of children are influenced by their parents' dietary habits (Scaglioni, Salvioni, & Galimberti, 2008) and the most important factor in the increase of BMI in children is the parents' BMI (Haney and Erdoğan, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sorular ile sorgulandı. Form araştırmacı tarafından literatür doğrultusunda oluşturuldu (12,13). Diyabet eğitim bilgi formu; eğitimi karşılaştırmak için araştırmacılar tarafından hazırlandı.…”
Section: Materyal Ve Metodunclassified